SIMULTANEOUS DETERMINATION OF AMILORIDE HYDROCHLORIDE AND HYDROCHLOROTHIAZIDE IN PHARMACEUTICALS BY DERIVATIVE SPECTROPHOTOMETRY - Al-Saidi, Khaleda H; Abdlaziz, Suhad; Semer, Sahar (Al-Nahrain Journal of Science, 2018)
Method is established for simultaneous determination of Amiloride hydrochloride (Amilo) andhydrochlorothiazide in tablets. The method is based on employing normal and derivativespectrophotometry using the zero order via described by measuring the absorbance at 361 nm andthe first order derivative spectra at peak 340 and valley 382 nm for (Amilo), while the zerocrossingmethod is applied for hydrochlorothiazide. The first order derivative absorption spectra atvalleys 285 and 239 nm were used for hydrochlorothiazide. No interferences found betweenboth determined and those of matrices. A good accuracy and precision of simultaneousdetermination of (Amilo), and hydrochlorothiazide were confirmed by statistical analysis. Thepercentage recovery of the individual drags under the established conditions is ranged from 97.79%to 101.5 %. Linearity is maintained within a wide concentration range from 2.00 mg/L to 40.00mg/L for Amiloride hydrochloride and hydrochlorothiazide. The detection limit was 0.5 and 1.0mg/L for Amiloride hydrochloride and hydrochlorothiazide respectively.